Genetics of inflammatory bowel disease. - Satsangi, J; Parkes, M; Jewell, D; Bell, J (1998)
1. The aetiology of the chronic inflammatory bowel diseases, Crohn's disease and ulcerative colitis, is uncertain. Studies of specific environmental factors and immune dysfunction have provided little insight into disease pathogenesis. 2. Concordance rates in twin pairs and siblings provide strong evidence that genetic factors are important in disease pathogenesis. In Oxford, information was obtained from 433 adult patients with Crohn's disease. Compared with the prevalence in the general population, the relative risks in siblings of patients with Crohn's disease calculated from these data were respectively 36.5 for Crohn's disease, 16.6 for ulcerative colitis and 24.7 for inflammatory bowel disease. 3. Clinical patterns of disease were compared in members of over 250 multiply affected families with inflammatory bowel disease. A high degree of concordance for many characteristics was noted (disease type, extent, extra-intestinal manifestations). However, in 77 affected parent-child pairs, the median age of onset in the parents was significantly higher than in offspring (P < 0.0001). These data reflect the results from other studies throughout the world, and are consistent with the phenomenon of genetic anticipation. 4. A detailed study investigating the contribution of the major histocompatibility complex was undertaken. Eighty-three affected sibling pairs were involved in a linkage analysis study; 348 patients with inflammatory bowel disease and 472 controls were involved in a detailed allelic association study. These data provide evidence that the major histocompatibility complex is an important determinant in ulcerative colitis, but not in Crohn's disease. 5. Cytokine genes are important candidate genes in inflammatory bowel disease. Allelic association study was performed to investigate the contribution of the gene encoding the interleukin-1 receptor antagonist and tumour necrosis factor-alpha. These data do not suggest that these genes encode important determinants of disease susceptibility in inflammatory bowel disease. 6. A two-stage genome-wide search for susceptibility loci in inflammatory bowel disease was performed involving 186 affected sibling pairs. The data provide strong evidence for the model of Crohn's disease and ulcerative colitis as related polygenic disorders. Loci on chromosomes 3, 7 and 12 were linked to inflammatory bowel disease overall, whereas loci on chromosomes 2 and 6 were linked only in ulcerative colitis. Linkage with chromosome 16 was noted in Crohn's disease only. Fine mapping of these susceptibility loci is in progress, and may lead to gene identification with attendant clinical benefits.